Pemilihan dan Implementasi Strategi Peningkatan Kenyamanan Termal Ruang Kuliah - Lusi Susanti; Hary Fandeli (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2017)
Optimum conditions help us think and work better. Thermal comfort in lecture buildings is important to maintain students’s comfort and help them concentrate on study. The fastest way to achieve expected thermal comfort inside the lecture room is using air conditioner, however, compensation on high electricity bills and degradation of the environmental quality has to be made. Therefore, the aim of this paper is to find and promote several environmental friendly strategies which can provide comfort to users in one hand, but also can reduce energy consumption in another hand. There have been several strategies in records to increase thermal comfort in buildings. To select the best and the most appropriate alternative, Analytical Hierarchy Process method was used by setting the criteria, sub-criteria, and alternatives to increase thermal comfort in lecture buildings of Andalas University. To test the selected alternative, thermal comfort inside two lecture rooms were evaluated experimentally. The comfort level was evaluated using PMV (Predicted Mean Vote) and PPD (Predicted Percentage Dissatisfied) model. For all experimental conditions, PMV and PPD results and individual thermal vote results showed a good match statistically meaning that the PMV and PPD models could predict thermal condition inside the lecture rooms. Results also showed that the presence of natural vegetation infront of glass windows of the lecture rooms statistically improved thermal comfort sensations of students under natural ventilation mode and reduced thermostat setting under air conditioning mode.